Biotic inactivation of the Pseudomonas aeruginosa quinolone signal molecule. (28th April 2015) - Soh, Eliza Ye‐Chen; Chhabra, Siri R.; Halliday, Nigel; Heeb, Stephan; Müller, Christine; Birmes, Franziska S.; Fetzner, Susanne; Cámara, Miguel; Chan, Kok‐Gan; Williams, Paul
Summary: In P seudomonas aeruginosa, quorum sensing (QS) regulates the production of secondary metabolites, many of which are antimicrobials that impact on polymicrobial community composition. Consequently, quenching QS modulates the environmental impact of P . aeruginosa . To identify bacteria capable of inactivating the QS signal molecule 2‐heptyl‐3‐hydroxy‐4(1 H )‐quinolone (PQS), a minimal medium containing PQS as the sole carbon source was used to enrich a Malaysian rainforest soil sample. This yielded an A chromobacter xylosoxidans strain (Q19) that inactivated PQS, yielding a new fluorescent compound (I‐PQS) confirmed as PQS‐derived using deuterated PQS. The I‐PQS structure was elucidated using mass spectrometry and nuclear magnetic resonance spectroscopy as 2‐heptyl‐2‐hydroxy‐1, 2‐dihydroquinoline‐3, 4‐dione (HHQD). A chromobacter xylosoxidans  Q19 oxidized PQS congeners with alkyl chains ranging from C1 to C5 and also N ‐methyl PQS, yielding the corresponding 2‐hydroxy‐1, 2‐dihydroquinoline‐3, 4‐diones, but was unable to inactivate the PQS precursor HHQ. This indicates that the hydroxyl group at position 3 in PQS is essential and that A . xylosoxidans inactivates PQS via a pathway involving the incorporation of oxygen at C2 of the heterocyclic ring. The conversion of PQS to HHQD also occurred on incubation with 12/17 A . xylosoxidans strains recovered from cystic fibrosis patients, with P . aeruginosa and with A rthrobacter, suggesting that formation of hydroxylated PQS may be a common mechanism of inactivation.